EFFECT OF MARKET DYNAMICS ON WAREHOUSE MANAGEMENT IN SAUDI ARABIA: A CASE OF UNIVERSAL MOTORS AGENCIES (UMA) - Tala Bajunaid; Ahmed Attia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The evolution of the market has dynamicity influences the finances and operations of the company. Thus, warehouse management plays a key role in determining the performance of the organization. The aim of this study is to test the effect of market dynamics on the warehouse management. The research used quantitative methodology whereby 30 employees of Universal Motors Agencies (UMA) in Jeddah, KSA were participated in the questionnaire survey. This study used correlation analysis to identify the presence of a relationship between the market dynamics and the complexity of the decision, the sophistication of the control, and the planning extensiveness. Besides that, this study also explores the presence of the causality between the market dynamics as independent variable and the complexity of the decision, the sophistication of the control, and the extensiveness of planning. The findings showed that market dynamics do not have a significant effect associated with that of warehouse management. There is a positive strong correlation between the market dynamics and the decision rule complexity (0.772) and a medium negative correlation between the market dynamics and control sophistication (-0.407). Despite the presence of the significant correlation, the paper does not find a significant impact of the market dynamics on the Decision Complexity, the Control Sophistication, and Extensive Planning. The results imply that there is a correlation but no causality, which implies the presence of other variables that are correlated with these variables and cause the change in the dependent variables.